2015
DOI: 10.1002/ajp.22487
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup genetic relatedness in two howler monkey species (Alouatta pigraandA. palliata): Implications for understanding social systems and dispersal

Abstract: The degree of genetic relatedness among group members is influenced by dispersal, group formation and composition, mating systems, and other socioecological factors. Making inferences about differences between species in their socio-genetic structure is difficult because studies rarely compare multiple species. In this study, we use multilocus microsatellite genotype data to analyze intragroup genetic relatedness in two howler monkey species (Alouatta palliata and A. pigra). We test the prediction that their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
(96 reference statements)
2
15
0
Order By: Relevance
“…The genetic diversity found in our two studied species was surprisingly high (He ∼ 80%, AR ∼ 9) given the restricted sampling area surveyed, and including social units comprising individuals not completely unrelated. Although a few population genetic studies with equally fine scale sampling have shown similar heterozygosity values (He = 0.71 to He = 0.81: Lagothrix lagotricha , Saguinus mystax , Saguinus weddelli , and Saimiri oerstedii (Blair & Melnick, ; Di Fiore & Fleischer , ; Garber, Porter, Spross, & Di Fiore, ; Huck et al, ), the published genetic diversity has been relatively lower (He = 0.56 to He = 0.64) in the majority of the New World monkeys studied, including other Saguinus and Alouatta species (e.g., Diaz‐Munoz, ; Hagell, Whipple, & Chambers, ; Milton, Lozier, & Lacey, ; Nidiffer and Cortes‐Ortiz ; Ruiz‐Garcia et al, ; Van Belle et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The genetic diversity found in our two studied species was surprisingly high (He ∼ 80%, AR ∼ 9) given the restricted sampling area surveyed, and including social units comprising individuals not completely unrelated. Although a few population genetic studies with equally fine scale sampling have shown similar heterozygosity values (He = 0.71 to He = 0.81: Lagothrix lagotricha , Saguinus mystax , Saguinus weddelli , and Saimiri oerstedii (Blair & Melnick, ; Di Fiore & Fleischer , ; Garber, Porter, Spross, & Di Fiore, ; Huck et al, ), the published genetic diversity has been relatively lower (He = 0.56 to He = 0.64) in the majority of the New World monkeys studied, including other Saguinus and Alouatta species (e.g., Diaz‐Munoz, ; Hagell, Whipple, & Chambers, ; Milton, Lozier, & Lacey, ; Nidiffer and Cortes‐Ortiz ; Ruiz‐Garcia et al, ; Van Belle et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Howler monkey species live in multi‐male/multi‐female groups of variable size (Brockett, Horwich, & Jones, ; Clarke & Glander ; Horwich, Brockett, & Jones, ; Pope ; Van Belle, Estrada, Strier, & Di Fiore, ). They are characterized by bisexual dispersal with variation in the direction and degree of sex bias across species and environmental conditions (e.g., Clarke & Glander, ; Glander, ; Nidiffer & Cortes‐Ortiz, ; Oklander, Kowalewski, & Corach, ; Pope, , ; Van Belle et al, ). Tamarins, by contrast, tend to live in familial social groups, that consist of several breeding‐age males and females within a functionally polyandrous single female‐breeding system (French, Inglett, & Dethlefs, ; Goldizen, ; Goldizen, Mendelson, vanVlaardingen, & Terborgh, ; Huck, Lottker, Bohle, & Heymann, ; S. F. Ferrari & Ferrari, ; Sussman & Garber, ).…”
Section: Introductionmentioning
confidence: 99%
“…Under this scenario, local resource competition and cooperation should have a minor influence on sex allocation. In well‐studied populations, however, related individuals often live in the same groups and kinship relationships affect social relationships (e.g., Cristóbal Azkarate et al, ; Dias et al, ; Lecompte, Bouanani, de Thoisy, & Crouau‐Roy, ; Nidiffer & Cortés‐Ortiz, ; Pope, , ; Rudran & Fernández‐Duque, ; Van Belle, Estrada, & Di Fiore, ; Van Belle, Estrada, Strier, & Di Fiore, ). For instance, in both black and ursine howler monkeys, females actively recruit females from their own matrilines and force the daughters of other females to emigrate (Crockett, ; Horwich, Brockett, James, & Jones, ; Rumiz, ).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting genetic structure of a given population and, in particular, the relatedness within and among social groups is not straightforward to predict from a particular type of social organization, however, because species vary in sex‐specific reproductive skew and dispersal pattern, adult sex ratio and other demographic characteristics (Greenwood 1980; Nonacs and Hager 2011; Di Fiore 2012; Liker et al. 2013; Nidiffer and Cortés‐Ortiz 2015). Information on genetic structure can therefore reveal insights about social units, population structure, and social behavior that are not obvious from behavioral and demographic data alone (Gompper et al.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral and demographic data can be used to describe how individuals are distributed in space and time, and solitary, pair-living, and group-living species are recognized as fundamental units of categorization of interspecific variation in social organization (Crook 1970). The resulting genetic structure of a given population and, in particular, the relatedness within and among social groups is not straightforward to predict from a particular type of social organization, however, because species vary in sexspecific reproductive skew and dispersal pattern, adult sex ratio and other demographic characteristics (Greenwood 1980;Nonacs and Hager 2011;Di Fiore 2012;Liker et al 2013;Nidiffer and Cort es-Ortiz 2015). Information on genetic structure can therefore reveal insights about social units, population structure, and social behavior that are not obvious from behavioral and demographic data alone (Gompper et al 1997;Caniglia et al 2014).…”
Section: Introductionmentioning
confidence: 99%